Impact of live attenuated influenza vaccination programme for healthy children in Northern Ireland: A comparison of seven influenza seasons, 2010/11–2016/17. Issue 4 (25th January 2018) - Gallagher, Naomh; Jessop, Lucy; Sartaj, Muhammad; Johnston, Jillian
Abstract: Seasonal influenza vaccination for healthy children was introduced in Northern Ireland in the 2013/14 flu season, with an initial pilot year involving two specific cohorts, followed by rollout to all children aged 4–11 years in subsequent seasons. This study aimed to examine the impact of that programme on the burden of flu in primary care over the study period 2010/11–2016/17. Two routine indicators were used to measure impact – GP in-hour consultations and out-of-hour calls for influenza and influenza-like-illness (ILI). Analysis was conducted overall and stratified by age; rates in children under 14 years of age to measure direct impact and rates in individuals 14 years and over to measure indirect impact. Seven influenza seasons were included, three pre-programme seasons (2010/11–2012/13: phase 0), one pilot season (2013/14: phase 1), and three post-programme seasons (2014/15–2016/17: phase 2). High uptake of vaccination was observed from the programme introduction, with consistent uptake of over 50% in pre-school age groups and over 75% in primary school age groups. Statistically significant reductions were found in GP in-hours consultations and in out-of-hour calls in phase 2 compared to phase 0, both overall (GP in-hours RR 0.61, 95% CI 0.38–0.98, p = .040; out-of-hours RR 0.51, 95% CI 0.27–0.97, p = .041) and in the under 14 years group (GP in-hours RR 0.38, 95% CI 0.19–0.75, p = .006; out-of-hours RR 0.39, 95% CI 0.19–0.83, p = .014). Our results suggest that there have been reductions in the burden of flu in primary care settings overall and in children aged under 14 years in the seasons since the introduction of healthy children influenza vaccination. Further seasons should be added to subsequent analyses to strengthen this evidence.